Corporate risk management - Merna, Tony (Wiley, 2008)
The book analyzes, compares, and contrasts tools and techniques used in risk management at corporate, strategic business and project level and develops a risk management mechanism for the sequencing of risk assessment through corporate, strategic and project stages of an investment in order to meet the requirements of the 1999 Turnbull report. By classifying and categorizing risk within these levels it is possible to drill down and roll-up to any level of the organizational structure and to establish the risks that each project is most sensitive to, so that appropriate risk response strategies.